How effective are expert patient (lay led) education programmes for chronic disease?. Issue 7606 (14th June 2007) - Griffiths, Chris; Foster, Gill; Ramsay, Jean; Eldridge, Sandra; Taylor, Stephanie
Abstract : Considerable hyperbole has surrounded the UK expert patient programme, and it has received considerable funding—but will its impact meet expectations?